Electrical characterization of the Macusanite volcanic glass and influence of nuclear fission tracks on electrical conductivity - de Oliveira, Vinicius Jessé Rodrigues [UNESP]; Pereira, Luiz Augusto Stuani [UNESP]; da Silva, Edilene Assunção [UNESP]; Sáenz, Carlos Alberto Tello [UNESP]; de Almeida Olivati, Clarissa [UNESP] (Elsevier, 2020)
Direct current dielectrical measurements were performed on samples of natural volcanic glass Macusanite with and without previous heat treatment at 650 °C for 10 h. Samples were analyzed via Source Measure Unit Keithley 238 instrument, which applies a voltage to provide the corresponding current. Moreover, the electrical measurements were also performed on a fission-induced irradiated sample in order to investigate the influence of the latent nuclear tracks on the electrical conductivity and activation energy of the glass with increasing temperature. The electrical characterization showed the characteristic insulating behavior of the glass: high resistance and low conductivity. However, after the sample was irradiated the electrical characterization provided a lower activation energy, which leads to better conductivity of the sample with increasing temperature. This enhancement in the glass conductivity with increasing temperature may be attributed to the latent nuclear tracks induced by irradiation, which favors the mobility of electric charges in the glass, and to the vibration frequency of the ions in the reorganized atomic structure after the glass was thermally treated.
Keywords: Electrical measurements; Heat treatment; Macusanite; Nuclear tracks